PENGARUH TATA KELOLA PERUSAHAAN DAN MANAJEMEN LABA TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL - Kartika Septiary Pratiwi Musa; Erwin Saraswati; Roekhudin Roekhudin (SIMAK, 2020)
This research aims to test corporate governance and earning management to corporate social responsibility disclosure. Sample on this resesarch are 62 manufacturing companies and is family company that chosen by purposive sampling method. According to the analysis result, this research shows that earning management has positive and significant impact to corporate social responsibility disclosure and corporate governance that proxied with board of commissioner stated that there is positive relation on corporate social responsibility disclosure, on independent commissioner proportion doesn’t affect significantly to corporate social responsibility disclosure, and on audit committee has significant impact on corporate social responsibility disclosure.